2015
DOI: 10.1007/s13213-015-1120-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic study of potentially bacteriocinogenic clinical and dairy Enterococcus spp. isolates from Bulgaria

Abstract: A total of 424 Enterococcus spp. isolates from clinical samples (n =398) and traditional Bulgarian artisanal cheeses (n=26) were studied in order to evaluate the incidence and expression of bacteriocin genetic determinants. Structural genes coding for enterocin A (entA), enterocin P (entP), enterocin B (entB), enterocin AS-48 (as-48) and enterolysin A (entlA) were detected by polymerase chain reaction (PCR), while reverse transcription PCR was performed to establish the gene expression. Of the total isolates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…diacetylactis were dominant isolates from raw‐milk Arzúa‐Ulloa cheeses (Menéndez, Centeno, Godinez, & Rodriguez‐Otero, ), which is in accordance with our research. Giraffa () and Strateva et al () noticed that, among enterococci, E. faecium and E. faecalis were generally the most frequent and prevalent species isolated from cheeses, which was also confirmed in our paper.…”
Section: Discussionsupporting
confidence: 90%
“…diacetylactis were dominant isolates from raw‐milk Arzúa‐Ulloa cheeses (Menéndez, Centeno, Godinez, & Rodriguez‐Otero, ), which is in accordance with our research. Giraffa () and Strateva et al () noticed that, among enterococci, E. faecium and E. faecalis were generally the most frequent and prevalent species isolated from cheeses, which was also confirmed in our paper.…”
Section: Discussionsupporting
confidence: 90%
“…Although EntB was first isolated from E. faecium T136 of a Spanish dry sausage, it has also been found in cheese samples and among clinical isolates [55,56,58]. Freitas et al (2016) and Strateva et al (2015) described the presence of EntB as infrequent in VREfm and VSEfm clinical isolates [56,57]. Regarding the first study, the VREfm isolates harboring EntB were mostly from Latin America, thus suggesting the possibility of a regional spread of particular clones (EntB was occasionally located on the chromosome) or plasmids [56].…”
Section: Class Ii-other Bacteriocinsmentioning
confidence: 99%
“…Although there is a clear lack of surveillance studies analyzing the distribution of this and other enterocins among enterococci, especially from clinical samples, Freitas et al (2016) reported a high incidence of EntA in outbreak VREfm and vancomycin-susceptible E. faecium (VSEfm) obtained from hospitalized patients in different countries over the last decades [56]. Likewise, Strateva et al (2015) reported a high incidence of EntA in clinical E. faecium isolates from various Bulgarian hospitals [57]. Indeed, EntA has been suggested to be part of the core genome of E. faecium [58], being chromosomally located, suggesting it may provide a competitive niche advantage to this species.…”
Section: Class Iia-the Pediocin-like Bacteriocinsmentioning
confidence: 99%
See 2 more Smart Citations